การศึกษาความเป็นไปได้ทางการเงินของสวนป่าพลังงาน สถานีพลังงานชีวมวล ชุมชนนาหว้า ตำบลนาหว้า อำเภอภูเวียง จังหวัดขอนแก่น - ปาณมาลา, พัณบงกช; หฤทัยธนาสันติ์, มะลิวัลย์; แหลมสัก, นิคม (วารสารวนศาสตร์ไทย, 2016)
This research aimed finding out pattern models for suitable and sufficient energy forest plantations. Finding out analyzing the capital and financial benefits obtained from the investment. And recommending methods for administering and managing energy forest plantations, by specifying the area for energy forest plantations within 30 kilometers from the established area for biomass-energy community station, covering 2 provinces, 15 districts, and 79 sub-districts. The area planned for energy forest plantations is approximately more than 2,200 rais. The energy forest plantations by eucalypt plantation for use as fuel to generate electricity. And also analying the financial returns and switching value test that affect the investment of NPV B/C ratio IRR and SVT (SVTb and SVTc). The results showed that the financial feasibility of energy plantations from eucalypt plantation. The financial rate of return that affec4 levels t investment of 700, 750, 800 and 850 baht/tonne and at the 4 given interest rate which were 8,10,12, and 15% for period of 7 years planting period. At the rate of return of 700 baht/tonne the NPV were 310.75, -682.70, -1,002.80 and -1,401.70 Baht , B/C ratios were 0.98,0.96,0.94 and 0.91 SVTb were -0.02,-0.04, -0.06 and -0.10 SVTc were -0.02,-0.04,-0.06 and -0.08. IRR was 6.53 which less than the interest rate at all levels that had investments risk. And at 750 baht/tonne, NPV were 1,108.75, 613.26, 183.33 and 358.42 Baht. B/C ratios were 1.05, 1.03, 1.01 and 0.98. SVTb were -0.02,-0.04,-0.06 and -0.10 SVTc were -0.02, 0.04, -0.06 and -0.09. IRR was 12.95 which was greater than the interest rate.There was no risk, but lacked of incention to invest. And at 800 baht/tonne NPV were 2,528.25, 1,909.22, 1,369.48 and 684.87 Baht. B/C ratios were 1.13, 1.11, 1.08 and 1.04. SVTb were 0.11, 0.09, 0.07 and 0.04. SVTc were 0.13, 0.10, 0.08 and 0.04. IRR was 18.75 which was greater than the interest rate no risk, as well as a reasonable return and there was a great incention for investment. And at 850 baht/tonne, NPV were 3,947.75, 3,205.18, 2,555.63 and 1,728.15 Baht B/C ratios were 1.20, 1.17, 1.14 and 1.108. SVTb were 0.16, 0.14, 0.13 and 0.10. SVTc 0.20, 0.17, 0.14 and 0.11. IRR was of 24.10 which is higher than the interest rate of return on investment and high motivation. It may affect the cost of power from biomass power stations. So, at the rate of return of 800 baht/tonne, that was suitable and motivating investment decisions. Reforestation energy by Eucalypust plantation for either investor or farmer is enormous